A study of passengers' satisfaction on airport service quality - Chong, Mun Jie; Sabar, Rohafiz (2012)
The fast growth number of air transportation and air passengers require better service from airports.Previously, academic literatures are seldom concentrated on airport service quality because of lack of competition among airports. There is unexplored field on the airport service. Airport service is a “green field” that waiting to be explored. The study is to determine the factors contribute to airport service quality influence passengers’ satisfaction and develop a theoretical framework for improve airport service quality.The study used the secondary data collected from literatures related to airport service. The study successful determined factors of airport service quality and develop a theoretical framework.